Workload Analysis on Employee Performance to Determine the Optimal Number of Employees by Using Full-Time Equivalent and NASA-TLX at PT. Z - Rizka Hafizah; Hery Hamdi Azwir (JIE Scientific Journal on Research and Application of Industrial System, 2022)
Human resources are the most valuable asset for companies to improve the quality of products or services, so optimizing an effective workforce is an effort to maintain performance. With the increasing demand for certification, the number of officers needed will also increase. Then it became a problem of uneven workload assigned to officers in the PCC division of PT. Z. To achieve maximum productivity and performance, this study was conducted to know the factors causing the mental workload, and also to calculate the optimal number of officers according to the competencies and responsibilities of each officer. The NASA-TLX method will be used to subjectively determine the weight of the workload. Based on the results of the NASA-TLX calculations, the average WWL is up to 71.4 which is classified as the 'Overload' category. Two of the three officers are classified as overload with a total WWL of each position being 79.67 and 81.67. Meanwhile, the Full-Time Equivalent method is used to determine the workload related to the work itself, performance, and allowance factors. Based on the results of the FTE calculation, it shows that two of the three officers are also categorized as 'overload' with each index being 1.63 and 2.42. The results of the FTE index show that the optimal number of officers requires hiring 2 people for each position in certification and quality management. The company should review the activity elements of each work unit and move the activity elements from the overload officer to the underload officer to get a normal workload